Anatomies of revolution - George Lawson (New York, NY Cambridge University Press, 2019)
"There are two main ways of approaching the study of revolution in the contemporary world - and they are both wrong. On the one hand, revolutions appear to be everywhere: on the streets of Kobane, Caracas, and Tehran; in the rhetoric of groups like Podemos and Black Lives Matter; and in the potential of technologies to reshape people's lives. Rarely do weeks go by without a revolution of one kind or another being proclaimed. In recent years, figures as varied as Abu Bakr al-Baghdadi, Emmanuel Macron, Tarana Burke, Xi Jinping, Tawakkol Karman, and Elon Musk have been labelled as revolutionaries, while the hugely popular musical Hamilton, and the even more popular Star War series, have eulogised revolutionary struggle. This broadening of the concept of revolution goes beyond its take-up by the mass media and in popular culture - www.revolution.com is a venture capitalist firm, www.revolution.co.uk is a software company, and www.revolution.com.au is a flea and heartworm treatment for dogs and cats. But is revolution really just a marketing trope, investment strategy, or pet service? And can it be street mobilization, social movement, and technological breakthrough at the same time? If revolution is everywhere, perhaps it is nowhere"-- Provided by publisher.
Includes bibliographial references.
Keywords: Revolutions--Social aspects